Born free and equal? : a philosophical inquiry into the nature of discrimination - Lippert-Rasmussen, Kasper, 1964- (Oxford University Press, 2014)
This text addresses these three issues: What is discrimination? What makes it wrong?; What should be done about wrongful discrimination? It argues that there are different concepts of discrimination; that discrimination is not always morally wrong and that when it is, it is so primarily because of its harmful effects.